Preclinical Evidence of the Efficacy of Lewis Y Car T Cells in Patient-Derived Models of Prostate Cancer - Risbridger, Gail Petuna (J Endocr Soc, 2021)
Chimeric antigen receptor T (CAR T) cell therapy is an adoptive immunotherapy that has led to new treatments for lymphoma, leukemia, and other blood cancers; however, its efficacy for prostate cancer remains unproven. Here we report pre-clinical evidence of the efficacy of CAR T cell therapy against the Lewis Y antigen (LeY) using patient-derived models of prostate cancer. To assess the expression of LeY on prostate tumours, we performed immunohistochemistry on a cohort of 41 patient-derived xenografts (PDXs). Cytoplasmic and membrane expression were separately assessed and quantified, for each patient. Overall, 61% (25/41) of PDXs were positive for membrane LeY expression, of which 18 PDXs had greater than 50% membrane-positive cells, and considered most suitable to detection and stable binding by anti-LeY CAR T’s. To determine the in vitro sensitivity to CAR T cytotoxicity, we selected 4 PDXs with high and 2 PDXs with low LeY expression using 3 androgen receptor (AR)-positive adenocarcinomas and 3 AR-negative tumors expressing neuroendocrine markers. Next we established organoids for in vitro co-culture assays where organoids were co-incubated with an equal number of anti-LeY+ CAR T cells or Empty vector control CAR T cells (Ev CAR T). Using time-lapse microscopy we reported destruction of organoids by LeY+ CAR T cells as indicated by their morphological collapse and uptake of propidium iodide from the culture medium; control Ev CAR T cells produced no cytotoxicity. Over the 48h assay, the level of target cell death of the LeY+ organoids was correlated to the intensity LeY surface expression. Target cell death mediated by the CAR T cells required perforin and granzyme B, as potent and highly specific small molecule inhibitors of perforin (SN34960) and granzyme B (C20) applied alone or in combination greatly decreased PI uptake, indicating organoid survival. Neither inhibitor adversely affected CAR T cell viability as measured by PI and Annexin V staining. This demonstrated canonical activation of granule exocytosis pathway by the CAR T cells, leading to organoid cell death. To assess CAR T cell efficacy in vivo, we selected one PDX with high LeY expression. Monotherapy with CAR T cells failed to decrease tumour volume compared to vehicle control. However, CAR T cells given after a single dose of the chemotherapeutic agent carboplatin greatly and durably reduced tumour burden, with residual tumour mass being less than 1% of their original size (0.56 ± 0.23% of tumour volume at the start of treatment). Overall, these data provide preclinical evidence that: i) high membrane expression of LeY correlates with in vitro and in vivo CAR T cell-induced tumour cell death via the canonical perforin/granzyme B mechanism; and, ii) membrane LeY can be used as a biomarker for patient selection.